REVIEW ARTICLE ON ARBUDA AND ITS AYURVEDIC MANAGEMENT IN VEDIC CONTEXT - Suresh Kumar Jat; Shikha Sharma; Tulika Sharma (Journal of Biomedical and Pharmaceutical Research, 2020)
Arbuda (cancer) is one of the most asadhya vyadhi in 20th century and spreading further with continuance and increasing incidence in the 21st century. The word Cancer is derived from the Greek meaning ‘CRAB’. Cancer is not new term in Ayurveda .It had already described by great trio of our acharya such as charak samhita, sushruta samhita, asthang hridya. The father of Indian surgery is acharya Sushruta which mentioned granthi and arbuda,In modern it resemble with cancer. Cancer as inflammatory or non-inflammatory swelling and mention them as either Granthi (minor neoplasm) or Arbuda (major neoplasm). Recent study shows that 7 lakh people died with cancer every year in India and mortality rate is higher in male than female. Keywords: Ayurveda, Arbuda, granthi, cancer.